The Optimum Conditions for Pleurotin Production by Pleurotus spp. Local Isolates - A. Al-Temimay, Israa; AL-Jibouri, Muna H.; A. Hassan, Abdulla; I. Mohammad, Farooq (Iraqi Journal of Science, 2023)
The study includ selection of six species of the fungi related to genus Pleurotus were evaluated for their ability to produce of Pleurotin, one of them, Pleurotus ostreatus (P.11) was isolated and identified in the present study. Pleurotin was detected by Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography (HPLC). The maximum absorption of Pleurotin was 1.6 nm at 250 nm. Pleurotin was purified with two methods using chloroform and ethyl acetate, the results showed the ethyl acetate was more efficient in pleurotin production resulting in 14.6 μg/ml compared to 9.8 μg/ml with chloroform. The local isolate, P. osteratus (P.11) showed significant high Pleurotin production (14.6 μg/ml) when was grown on the modified Czapek-Dox liquid media supplemented with 5% sawdust compared to (0-7.8 μg/ml) the rest fungi in the same medium. By screening various growth conditions, production of Pleurotin by P. ostreatus (P.11) increased to 38.5 μg/ml using modified Czapek-Dox liquid medium supplemented with 10% Rice husks, pH 7, incubation for 5 weeks at 30 °C.